KAJIAN YURIDIS PUBLIKASI FILM DI INTERNET TANPA IZIN PEMEGANG HAK CIPTA DITINJAU DARI UNDANG - UNDANG HAK CIPTA NO 28 TAHUN 2014 - Muhammad Kemal Fasya; Komang Febrinayanti Dantes; Muhamad Jodi Setianto (Universitas Pendidikan Ganesha, 2023)
This research aims to (1) determine the legal consequences of uploading copyrighted film works without the creator's permission on the Internet (2) legal remedies that can be taken by copyright holders regarding copyright violations in films or cinematography published on the internet without the creator's permission. The type of research used is normative legal research, namely legal research carried out by examining library materials or secondary data. The sources of legal materials used are (1) Primary legal materials, namely legal materials consisting of statutory regulations. (2) Secondary legal materials, namely legal materials consisting of books, legal journals, opinions of scholars (doctrine), legal cases, jurisprudence, and the results of the latest symposia, which are related to research problems. (3) Tertiary legal materials, namely legal materials that provide instructions or explanations for primary legal materials and secondary legal materials. Management and analysis of legal materials where the data obtained is ordered data which is analyzed using qualitative analysis, namely after the data is collected it is then expressed in the form of a logical and systematic description, then analyzed to obtain clarity on problem solving. The results of this research show that there are still many cases of spreading film publications on the internet without permission, where the perpetrators publish films through various media on the internet, whether through film streaming websites or social media platforms such as YouTube, Facebook, Telegram, etc. This occurs due to a lack of awareness of respecting other people's creative works, where the perpetrators deliberately publish films without the creator's permission, apart from that, there is also a lack of understanding regarding the rules relating to film publication and the legal consequences arising from publishing films on the internet. without the creator's permission.